Allium stent as a curative treatment for benign ureteral strictures: Preliminary experience, surgical technique, and functional results - Salciccia, Stefano; De Marco, Ferdinando; Sciarra, Alessandro; Moriconi, Martina; Alfarone, Andrea; Polese, Milena; Maggi, Martina; Del Giudice, Francesco; Gentilucci, Alessandro; De Berardinis, Ettore; Ricciuti, Gian Piero (Frontiers in Urology, 2022)
Objectives: to evaluate the effectiveness and safety of Allium ureteral stent as a curative treatment of benign ureteral strictures. Materials and Methods: We retrospectively review the electronic database of two centres of patients who underwent ureteral Allium positioning for different type of stenosis (benign or malignant). Between April 2017 and May 2021, 151 patients were treated with Allium stent for ureteral strictures including benign and malignant stenosis. 83 of them met the inclusion criteria for benign ureteral stricture and were included in final analysis. Results: About the etiology of strictures, 79 (95.18%) were secondary to ureteroscopy or impacted stones, 4 (4.82%) secondary to pelvic surgery. The median operating time was 47.9 ±15.53 min, and the median length of strictures was 2.51±0.84 (1-4) cm. The median time of follow-up was 18 months (range 1-48 months), the overall success rate was 85.5 % (71/83) and no intraoperative or perioperative major complications were recorded. Among patients with failure (12 pts, 14.5%): 10 (83.33%) presented again ureteral strictures, among them 8/10 were patients with a stricture length between 2 and 4 cm, 2 (16.67%) patients with pyelus-ureteral junction (UPJ) stenosis experienced migration of the stent. All patients who experienced failure were treated surgically either with robotic or laparoscopic approach. Conclusions: in our preliminary experience, Allium stent seem be an effective and safe surgical treatment for benign ureteral stricture. Further analysis and prospective trials are necessary to better define the role of Allium stent in the treatment of benign ureteral strictures.